Earthquake Intensity Determination Based on Maximum Land Acceleration in Padang City Area Using Atkinson Boore Method (2003) - Linda Susanti; Syafriani, Syafriani; Hamdi, Hamdi; Dwiridal, Letmi (Department of Physics, Universitas Negeri Padang, 2024)
Geologically, the city of Padang had the potential for large earthquake impacts due to its location within the Sumatran Fault, Mentawai Fault, and above the Subduction Zone. The magnitude of earthquake damage was determined by soil quality factors and earthquake intensity. To determine the extent of damage, the maximum ground acceleration value was used. This value represented the maximum ground vibration acceleration that occurred at a specific location within a particular area, resulting from all earthquakes that occurred during a specific time period. The maximum ground acceleration value and earthquake intensity in the Padang City area could be calculated using the Atkhinson Boore (2003) method. This study was a quantitative research that commenced by examining relevant theories related to the issue at hand. The research then proceeded with the collection of secondary data obtained from the United States Geological Survey (USGS) website. Specifically, earthquake data for the period between 2000 - 2020 in the Padang City area with coordinates LS- LS and BT- BT, and a magnitude M ≥ 5.0 SR depth < 100 km were utilized. Historical earthquake data was employed to determine earthquake intensity values, which were then used to assess the earthquake risk in the Padang City area. Based on the calculation results, the maximum acceleration value of soil was found between 0.519001 g- 0.603847 g. The highest value of maximum acceleration of soil was located in Bungus Teluk Kabung area, while the lowest value was found in Koto Tangah area. The distribution of earthquake intensity (MMI) in Kota Padang area has a value of VIII MMI.